Studi Hasil Pemeriksaan Trigliserida pada Pasien Hipertensi Rawat Inap Di Rumah Sakit Umum Wisata Universitas Indonesia Timur - Rismaa Rismaa; Fransiska Nona Ita (Jurnal Media Laboran, 2020)
Hypertension or high blood pressure is an abnormal increase in blood pressure in a person's arteries. It is said to have high blood pressure if it exceeds the normal limit (12/80 mmHg). Triglycerides are a type of fat in the blood that serves as an energy reserve. The purpose of the study was to determine the results of triglyceride examination in hypertensive patients. This type of research is an observational laboratory using 3 samples of patients with hypertension. Where the results of the examination are above 200 mg/dl or abnormal with an average value of 276 mg/dl. The normal value for triglyceride levels is < 200 mg/dl.